Modulation of ipsilateral motor evoked potentials during bimanual coordination tasks - Altermatt, Miriam; Jordan, Harry; Ho, Kelly; Byblow, Winston D. (Frontiers in Human Neuroscience, 2023)
Ipsilateral motor evoked potentials (iMEPs) are difficult to obtain in distal upper limb muscles of healthy participants but give a direct insight into the role of ipsilateral motor control. We tested a new high-intensity double pulse transcranial magnetic stimulation (TMS) protocol to elicit iMEPs in wrist extensor and flexor muscles during four different bimanual movements (cooperativeasymmetric, cooperativesymmetric, non-cooperativeasymmetric and non-cooperativesymmetric) in 16 participants. Nine participants showed an iMEP in the wrist extensor in at least 20% of the trials in each of the conditions and were classified as iMEP + participants. iMEP persistence was greater for cooperative (50.5±28.8%) compared to noncooperative (31.6±22.1%) tasks but did not differ between asymmetric and symmetric tasks. Area and amplitude of iMEPs were also increased during cooperative (area = 5.41±3.4 mV*ms; amplitude = 1.60±1.09 mV) compared to non-cooperative (area = 3.89±2.0 mV*ms; amplitude = 1.12±0.56 mV) tasks and unaffected by task-symmetry. The upregulation of iMEPs during common-goal cooperative tasks shows a functional relevance of ipsilateral motor control in bimanual movements. The paired-pulse TMS protocol is a reliable method to elicit iMEPs in healthy participants and can give new information about neural control of upper limb movements.With this work we contribute to the research field in two main aspects. First, we describe a reliable method to elicit ipsilateral motor evoked potentials in healthy participants which will be useful in further advancing research in the area of upper limb movements. Second, we add new insight into the motor control of bimanual movements. We were able to show an upregulation of bilateral control represented by increased ipsilateral motor evoked potentials in cooperative, object-oriented movements compared to separate bimanual tasks. This result might also have an impact on neurorehabilitation after stroke.